Passion fruit oil (Passiflora edulis): Use of the seeds in cosmetic products (Enfoque UTE, 2020)
The work documented in this essay is focused on harnessing the properties of Passion fruit seeds Passiflora edulis f.flavicarpa Deg to achieve the design of a cosmetic product: an exfoliating cream containing passion fruit seed oil and solid residue generated from oil extraction. The applied methodology for the formulation of the cream was initially based on a combination of a mechanical process through pressing, and oil extraction from the seeds by the use of organic solvents, ethyl ether. The physicochemical analysis variables evaluated in the exfoliating cream were pH, extensibility and emulsion capacity. The physical properties were considered as listed, colour, odour, brightness and grittiness. Furthermore, the absence of lumps was evaluated as macroscopic indicators of adequate particle size distribution and uniform texture. It was concluded that the oil from passionfruit seeds due to its composition in protein and liquid elements, optimally conserves the inherent properties of a product designed for skincare and conditioning. The use of solid residue that for primary industries is considered as unstable waste, represents an innovative alternative in the range of available semi-finished raw materials with properties capable of enhancing the products for human consumption.